2022
DOI: 10.1111/aor.14270
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation during the first three waves of the coronavirus disease 2019 pandemic: A retrospective single‐center registry study

Abstract: Background Despite increasing knowledge about the optimal treatment for patients with severe COVID‐19, data from different cohorts suggested that survival of patients treated with ECMO seemed to decline over the course of the pandemic. Methods In this non‐interventional retrospective single‐center registry study we analyzed all consecutive patients tested positive for SARS‐CoV‐2 infection and supported with VV ECMO in our center during the first three waves of the pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(106 reference statements)
1
11
0
Order By: Relevance
“…Of these, 22 were excluded due to their focus on veno-arterial ECMO (V-A ECMO) or extracorporeal cardiopulmonary resuscitation (ECPR) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Fourteen studies were excluded for lack or scarcity of data on CytoSorb© use [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], four because of the lack of specific data for the ECMO subgroup [ 67 , 68 , 69 , 70 ], four because CytoSorb© was not used concomitantly with ECMO therapy [ 71 , 72 , 73 , 74 ], two because outcomes of interest for the simultaneous use of CytoSorb© and ECMO were not reported [ 75 , 76 ], and one because it focused on a different device [ 77 ]. One study was excluded because it only reported preliminary findings from other articles [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 22 were excluded due to their focus on veno-arterial ECMO (V-A ECMO) or extracorporeal cardiopulmonary resuscitation (ECPR) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Fourteen studies were excluded for lack or scarcity of data on CytoSorb© use [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], four because of the lack of specific data for the ECMO subgroup [ 67 , 68 , 69 , 70 ], four because CytoSorb© was not used concomitantly with ECMO therapy [ 71 , 72 , 73 , 74 ], two because outcomes of interest for the simultaneous use of CytoSorb© and ECMO were not reported [ 75 , 76 ], and one because it focused on a different device [ 77 ]. One study was excluded because it only reported preliminary findings from other articles [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Data for waves 1–3 was reported previously. 4 During the fourth wave, in 10/29 patients (34%) the delta variant was detected, and only in one patient (3%) the omicron variant. For 18/29 patients (62%), no sequencing data was available.…”
Section: Tablementioning
confidence: 98%
“…The data come from a non‐interventional retrospective single‐center registry, as described previously. 4 We included all COVID‐19 patients supported with V‐V ECMO from the beginning of the COVID‐19 pandemic in our center in March 2020 until May 15, 2022. Indication for V‐V ECMO, standard treatment procedures and criteria for discontinuation of ECMO in our center followed established criteria and were applied unchanged throughout the COVID‐19 pandemic.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the PCR testing was repeated twice, and the results were negative. Also, it should be emphasized that ARDS caused by infection with this virus has some unique features, but much of the experience with severe respiratory failure in SARS-CoV-2 patients is not different from other forms of ARDS, and it is one of the indications for the VV-ECMO use [16]. Recent studies have shown that in patients infected with the SARS-CoV-2 and treated with ECMO the mortality in the first 60 days was about 31%, and a very similar result was obtained in the EOLIA study (35% in 60 days) [12].…”
Section: Case Reportmentioning
confidence: 99%